Kandidasi Calon Anggota Legislatif Perempuan DPRD Kabupaten Tegal Pada Pemilu 2024 (Studi Kasus : DPC PDIP Kabupaten Tegal) - Destyanti, Riris Dwi; Rohman, Ahmad Zaki Fadlur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The ratification of the Affirmative action policy and the Zipper system in the General Election in Indonesia has increased women's participation as legislative candidates. In the 2024 election in Tegal Regency, many women are running for office through the Indonesian Democratic Party of Struggle (PDIP). This research aims to identify and understand the candidacy process carried out by PDIP for female legislative candidates. This study uses a qualitative method with an explanatory case study approach. The analysis was carried out using the theory of Gideon Rahat and Reuven Y,